Implementation of Data Envelopment analysis (DEA) in measuring the efficiency zakat fund management - Tsalis Syaifuddin (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Negeri (IAIN) Salatiga, 2019)
This study aims to determine the efficiency level of management of zakat funds at the National Zakat Amil Agency (BAZNAS). The author uses the quantitative non-parametric Data Envelopment Analysis (DEA) method. Total assets, promotion, and documentation costs, and official travel costs as input variables. Whereas the output variance consists of receiving zakat funds and distributing zakat funds. The results showed that BAZNAS experienced efficiency in 2012-2014 and 2017 with a score of 100%. Inefficiencies occurred in 2015 at 79.16% and in 2016 amounted to 98.72%. In 2015-2016, all input variables experienced inefficiency, while the output variable was the only inefficient distribution of zakat funds. In overcoming, inefficiencies can be adjusted between the target and actual quantities specified in the DEA calculation. The author recommends that BAZNAS pay attention to the causes of inefficiency so that it can improve performance better.